Jet-jet interaction in multiple injections: A large-eddy simulation study. (15th December 2018) - Hadadpour, Ahmad; Jangi, Mehdi; Bai, Xue Song
Graphical abstract: Highlights: A high-momentum short post-injection reduces the near-nozzle residue gases. A low-momentum short post-injection enriches the near-nozzle over-lean mixture. The longer the dwell time, the lower the peak mass of the fuel-rich mixture. The cases with shorter dwell time and longer post-injection have more significant jet-jet interaction. Abstract: This paper reports on studies of multiple-injection strategies of gaseous fuel in a model combustion chamber and the role of jet-jet interactions on the mixing processes in the chamber using large-eddy simulation (LES). A high-pressure non-reacting gas flow injected through a jet with a nozzle diameter of 1.35 mm into a quiescent inert air environment is considered. First, we validate the method and our computational setup by comparing the simulation results of a single injection case with available experimental data. It is shown that the transient ensemble-averaged LES results agree well with the experimental measurements. Second, we simulate and compare fourteen injection strategies in order to understand the effect of the main and the post-injections duration, the dwell time and the mass flow rate of post-injection on the mixing, jet penetration, and near-nozzle mixture. The contribution of each injection in the local mixture composition is quantified by solving transport equations for the mixture fraction of each injection. The results show that the turbulence generated in the main injection is enhanced when the post-injection flow into the main injection flow. The increase of the local turbulence intensity is in favor of increasing the scalar dissipation rate and enhancing the mixing rate. However, the penetration of the post-injection flow into the main injection flow and the level of the gas flow from the interaction of two injections depend on the dwell time and the momentum of the post-injection. The results also show that the post-injection modifies the near-nozzle mixture. The comparison of cases with different mass flow rates in the post-injection indicates that the momentum of the post-injection can be optimized either to push away the near-nozzle remaining gas from the main injection and reduce the near-nozzle residue by more than 25 % or enrich this fuel-lean region and increase the near-nozzle gasses by more than 43 % . These results are very interesting for optimization of the post-injection to reduce engine-out emissions.